Targeting Young Viewers to Watch Traditional Television. (November 2021) - Lum, Elliot; Martinez, Luisa; Soling, Marcia
Univision is a brand well-known to Hispanic viewers, but with fragmentation and so many choices within the media landscape, they had to break through the noise effectively. The challenge for Univision was to attract a younger demographic (18–34 year-olds) of loyal viewers to consume Spanish language programming by packaging the use of music and reggaeton in a new telenovela which would showcase premium content that appealed to audiences of all ages. They identified digital, social, radio, and out-of-home platforms consumed by these potential viewers to deliver content and awareness to bring the idea to life. The results exceeded all programming and sales estimates, grew the timeslot's ratings, and brought in a younger audience than any 8 pm telenovela.